Banana Dryer with Temperature and Time Control for Small and Medium Industries - Abd Razak, Nurul Atirah; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2025)
Pisang Salai is one of the famous dishes in the state of Johor because of its unique taste. The drying process is the main process in the production of pisang salai. Therefore, to ensure that the quality of pisang salai is not affected, the drying process of bananas must be carried out correctly. However, when the monsoon season arrives, the drying process will be affected due to the lack of light sources from the sun. Therefore, entrepreneurs want a new alternative that does not need to depend on light sources from the sun. In the development of this project, there are three main objectives, namely, designing, developing, and testing in terms of usability and functionality of the prototype to be developed. The purpose of this project is to help entrepreneurs overcome the problems that they faced. The Design Thinking model was chosen as a guideline throughout the prototype development process. An Arduino ESP32 microcontroller is used as a controller unit to control the system. In addition, the Blynk application is also used to further expand the use of IoT to the public. Overall, the prototype has been designed successfully and satisfies the research’s goals and if this product can be brought to market, it can also simplify things for those who operate pisang salai.